Development and Validation of Difference Spectrophotometric Method for Simultaneous Estimation of Rosuvastatin Calcium and Aspirin in Marketed Formulation - Padmavathi, R; Padmavathi, Y; Babu, N Raghavendra; Akhila, V; Keerthi, G (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: To develop and validate a simple Vierordt method for the simultaneous estimation of rosuvastatin calcium (RSV ca) and aspirin (ASP) in fixed dose combination capsules by difference spectrophotometry technique in the UV region. Difference spectrophotometry is based on the utilization of difference absorption spectra corresponding to the same compound obtained at two different pH values. Methodology: The difference in spectral characteristics for the two drugs was observed in 0.01N acetic acid and 0.01N NaOH. The simultaneous equations were developed using difference absorbance and absorptivity values of the two drugs measured and calculated at 243.2nm and 297nm for RSV ca and ASP respectively. Results: Two drugs have shown very good linearity in the concentration range of 10-100µg/ml. The methods were validated as per ICH guidelines for the limit of detection, the limit of quantification, accuracy, and precision, which were found to be within the acceptable limits. The validated method was successfully applied for the analysis of rosuvastatin calcium and aspirin in fixed dose combination capsules. Conclusion: Because this approach is simple and does not require a particular programme, it can be used as a substitute for LC methods in quality control laboratories that lack the necessary equipment for those techniques.